Energy efficiency management in application to the Faculty of Electrical Engineering building at the Shah Alam UiTM campus / Mohd Razlan Khalid - Khalid, Mohd Razlan (2001)
This thesis describes a study of energy management to achieve better efficiency in application to the Faculty of Electrical Engineering building at the Shah Alam UiTM campus. It describes the techniques used to develop efficient energy consumption and improved and usage of the air-conditioning system. The lighting system proposed will be more energy efficient, cost effective and yields better lighting at low cost. Electricity is provided by TNB under its Cl tariff. The utility costs under this tariff are RM 17.30 per kilowatt of demand per month (KW) and RM 0.208 per kilo watt hour (KWh) of electricity. The result of an energy efficiency study performed for this building is summarized to be compared with the existing condition which is inefficient at present. A. cost estimate on was performed for each measure and the simple payback period was calculated.